2020
DOI: 10.3390/pharmaceutics12050400
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystals for Improved Drug Delivery of Dexamethasone in Skin Investigated by EPR Spectroscopy

Abstract: Nanocrystals represent an improvement over the traditional nanocarriers for dermal application, providing the advantages of 100% drug loading, a large surface area, increased adhesion, and the potential for hair follicle targeting. To investigate their advantage for drug delivery, compared to a base cream formulation, dexamethasone (Dx), a synthetic glucocorticoid frequently used for the treatment of inflammatory skin diseases, was covalently linked with the paramagnetic probe 3-(carboxy)-2,2,5,5-tetramethyl-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…Extending a previously introduced method ( 29 , 30 , 31 ), spatially resolved diffusivity and free-energy profiles are estimated from experimentally measured concentration profiles. Numerical profiles are computed by discretizing the entire experimental setup from the glass bottom of the substrate to the air-water interface ( z bot to − z top in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending a previously introduced method ( 29 , 30 , 31 ), spatially resolved diffusivity and free-energy profiles are estimated from experimentally measured concentration profiles. Numerical profiles are computed by discretizing the entire experimental setup from the glass bottom of the substrate to the air-water interface ( z bot to − z top in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We investigate the filtering function of hydrogels by theoretical analysis of time-resolved concentration profiles of the labeled dextran molecules as they penetrate into the hydrogel. The employed numerical method allows for simultaneous extraction of free-energy and diffusivity profiles from relative concentration profiles at different times and is a significant extension of earlier methods ( 29 , 30 , 31 ) because it does not require absolute concentration profiles but works with relative, i.e., arbitrarily normalized, concentrations. This is a crucial advantage because often fluorescence intensity profiles are subject to significant perturbation due to, e.g., laser light intensity fluctuations or fluorescence dye bleaching over the course of the experiment, and using relative concentrations makes the often-difficult conversion of measured intensity data into absolute particle concentrations obsolete.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that nanocrystals improve dermal bioavailability by increasing penetration through the skin. Due to the increased surface area of the nanocrystals, the dissolution rate increases, making it possible to maintain a large concentration gradient between the formulation and the skin, and thus forcing diffusion of the drug into the skin [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone (DEX) is a synthetic glucocorticoid used in a wide range of diseases [ 1 , 2 , 3 , 4 ], particularly when related with lung, from occlusive airway conditions such as asthma [ 5 ] to maturation of foetus lung [ 6 ]. Recent studies report that DEX can be profitably applied to the treatment of acute respiratory distress syndrome [ 7 ] and could reduce deaths among patients with serious cases of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The formulation of DEX in nano-carriers could improve the delivery of this insoluble drug to the targeted epithelial tissue. Different types of nanotechnologies have been developed, including the conjugation of DEX with a polymeric chain or a lipidic structure [ 12 , 13 , 14 , 15 , 16 , 17 ], as well as its encapsulation in solid nanoparticles, its inclusion in a solid matrix or its formulation as a small crystal evenly coated with a polymer [ 3 , 10 , 18 ]. In particular, formulations where DEX is hosted in a controlled crystalline solid core of a nanostructure show both improved solubility with respect to raw dexamethasone and an increased residence time as compared to its water-soluble analogous, dexamethasone-phosphate.…”
Section: Introductionmentioning
confidence: 99%